Mitigation pathways towards national ambient air quality standards in India. (December 2019) - Purohit, Pallav; Amann, Markus; Kiesewetter, Gregor; Rafaj, Peter; Chaturvedi, Vaibhav; Dholakia, Hem H.; Koti, Poonam Nagar; Klimont, Zbigniew; Borken-Kleefeld, Jens; Gomez-Sanabria, Adriana; Schöpp, Wolfgang; Sander, Robert
Abstract: Exposure to ambient particulate matter is a leading risk factor for environmental public health in India. While Indian authorities implemented several measures to reduce emissions from the power, industry and transportation sectors over the last years, such strategies appear to be insufficient to reduce the ambient fine particulate matter (PM2.5 ) concentration below the Indian National Ambient Air Quality Standard (NAAQS) of 40 μg/m 3 across the country. This study explores pathways towards achieving the NAAQS in India in the context of the dynamics of social and economic development. In addition, to inform action at the subnational levels in India, we estimate the exposure to ambient air pollution in the current legislations and alternative policy scenarios based on simulations with the GAINS integrated assessment model. The analysis reveals that in many of the Indian States emission sources that are outside of their immediate jurisdictions make the dominating contributions to (population-weighted) ambient pollution levels of PM2.5 . Consequently, most of the States cannot achieve significant improvements in their air quality and population exposure on their own without emission reductions in the surrounding regions, and any cost-effective strategy requires regionally coordinated approaches. Advanced technical emission control measures could provide NAAQS-compliant air quality for 60% of the Indian population. However, if combined with national sustainable development strategies, an additional 25% population will be provided with clean air, which appears to be a significant co-benefit on air quality (totaling 85%). Graphical abstract: Unlabelled Image Highlights: A large share of the Indian population lives with dangerous levels of air pollution. Effective impacts of existing controls are compensated by rapid economic growth. Effective solutions require coordination of urban, rural and inter-state responses. Available policies and measures may bring air quality under the NAAQS compliance. The sustainable development measures can deliver a wide range of co-benefits.